Nucleotide sequence and deletion analysis of the xylanase gene (xynZ) of Clostridium thermocellum. - Grépinet, O (1988)
The nucleotide sequence of the xynZ gene, encoding the extracellular xylanase Z of Clostridium thermocellum, was determined. The putative xynZ gene was 2,511 base pairs long and encoded a polypeptide of 837 amino acids. A region of 60 amino acids containing a duplicated segment of 24 amino acids was found between residues 429 and 488 of xylanase Z. This region was strongly similar to the conserved domain found at the carboxy-terminal ends of C. thermocellum endoglucanases A, B, and D. Deletions removing up to 508 codons from the 5' end of the gene did not affect the activity of the encoded polypeptide, showing that the active site was located in the C-terminal half of the protein and that the conserved region was not involved in catalysis. Expression of xylanase activity in Escherichia coli was increased up to 220-fold by fusing fragments containing the 3' end of the gene with the start of lacZ present in pUC19. An internal translational initiation site which was efficiently recognized in E. coli was tentatively identified 470 codons downstream from the actual start codon.